Occupational cataracts and lens opacities in interventional cardiology (O'CLOC study): are X-Rays involved? Radiation-induced cataracts and lens opacities - Jacob, Sophie; Michel, Morgane; Spaulding, Christian; Boveda, Serge; Bar, Olivier; Brézin, Antoine P; Streho, Maté; Maccia, Carlo; Scanff, Pascale; Laurier, Dominique; Bernier, Marie-Odile (BMC public health, 2010)
The eye is well known to be sensitive to clearly high doses (>2 Gy) of ionizing radiation. In recent years, however, cataracts have been observed in populations exposed to lower doses. Interventional cardiologists are repeatedly and acutely exposed to scattered ionizing radiation (X-rays) during the diagnostic and therapeutic procedures they perform. These "low" exposures may cause damage to the lens of the eye and induce early cataracts, known as radiation-induced cataracts. The O'CLOC study (Occupational Cataracts and Lens Opacities in interventional Cardiology) was designed to test the hypothesis that interventional cardiologists, compared with an unexposed reference group of non-interventional cardiologists, have an increased risk of cataracts. The O'CLOC study is a cross-sectional study that will include a total of 300 cardiologists aged at least 40 years: one group of exposed interventional cardiologists and another of non-interventional cardiologists. The groups will be matched for age and sex. Individual information, including risk factors for cataracts (age, diabetes, myopia, etc.), will be collected during a telephone interview. A specific section of the questionnaire for the exposed group focuses on occupational history, including a description of the procedures (type, frequency, radiation protection tool) used. These data will be used to classify subjects into "exposure level" groups according to cumulative dose estimates. Eye examinations for all participants will be performed to detect cataracts, even in the early stages (lens opacities, according to LOCS III, the international standard classification). The analysis will provide an estimation of the cataract risk in interventional cardiology compared with the unexposed reference group, while taking other risk factors into account. An analysis comparing the risks according to level of exposure is also planned. This epidemiological study will provide further evidence about the potential risk of radiation-induced cataracts at low doses and contribute to cardiologists' awareness of the importance of radiation protection. NCT01061463.